THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN HEALTHCARE (Global Conference on Medical and Health Sciences, 2026)
Artificial intelligence (AI) has emerged as one of the most influential technologies in modern healthcare. This paper explores the role of AI in improving medical diagnosis, treatment planning, and patient care. It examines key applications such as machine learning, medical imaging analysis, and predictive analytics. The study also discusses the benefits and challenges associated with AI implementation in healthcare systems. The findings suggest that AI enhances accuracy, efficiency, and decision-making in medicine, while also raising concerns about ethics, data privacy, and reliability. The paper concludes that AI will play a crucial role in the future of healthcare development.
Keywords: artificial intelligence, healthcare innovation, machine learning, medical diagnosis, predictive analytics, digital medicine, health technology, patient care.